Phase II Study of Adjuvant Immunotherapy with the CSF-470 Vaccine Plus Bacillus Calmette–Guerin Plus Recombinant Human Granulocyte Macrophage-Colony Stimulating Factor vs Medium-Dose Interferon Alpha 2B in Stages IIB, IIC, and III Cutaneous Melanoma Patients: A Single Institution, Randomized Study - Mordoh, José; Pampena, María Betina; Aris, Mariana; Blanco, Paula Alejandra; Lombardo, Mónica; von Euw, Erika María; Mac Keon, Soledad; Yépez Crow, Michelle; Bravo, Alicia Inés; O’Connor, Juan Manuel; Orlando, Ana Gabriela; Ramello, Franco; et al. (Frontiers in Immunology, 2017)
The irradiated, allogeneic, cellular CSF-470 vaccine plus BCG and rhGM-CSF is being tested against medium-dose IFN-alpha2b in stages IIB-III cutaneous melanoma patients after surgery in an open, randomized, Phase II/III study. We present the results of the Phase II part of the ongoing CASVAC-0401 study (ClinicalTrials.gov: NCT01729663). Thirty one patients were randomized to the CSF-470 vaccine (n=20) or to the IFN-alpha2b arm (n=11). During the 2-years treatment, immunized patients should receive 13 vaccinations. On day one of each visit, 1.6x107 irradiated CSF-470 cells plus 106 cfu BCG plus 100μg rhGM-CSF were administered intradermally, followed on days 2-4 by 100μg rhGM-CSF. IFN-alpha2b patients should receive 10 million units/day/5 days a week for 4 weeks; then 5 million units thrice weekly for 23 months. Toxicity and Quality of Life were evaluated at each visit. With a mean and a maximum follow-up of 39.4 and 83 months respectively, a significant benefit in the distant metastasis-free survival for CSF-470 was observed (p=0.022). Immune monitoring showed an increase in antitumoral cellular and humoral response in vaccinated patients. CSF-470 was well tolerated; 20/20 patients presented grades 1-2 dermic reactions at the vaccination site; 3/20 patients presented grade 3 allergic reactions. Other adverse events were grade 1. Patients in the IFN-alpha2b arm presented grades 2-3 hematologic (7/11), hepatic (2/11) and cardiac (1/11) toxicity; adverse events in 9/11 patients forced treatment interruptions. Quality of Life was significantly superior in the vaccine arm (p<0.0001). Our results suggest that CSF-470 vaccine plus BCG plus GM-CSF can significantly prolong, and with lower toxicity, the distant metastasis free survival of high risk cutaneous melanoma patients with respect to medium dose IFN-alpha2b. The continuation of a phase III part of the CASVAC-0401 study is encouraged.